The comparative analysis of traditional, “active”, and modern schools - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1998)
This article analyses the following three basic trends of school educational systems: traditional, "active" and modern schools. Based on comparative analysis, the article reviews the main principles of education, the content of teaching, forms and methods of its organization, attitudes towards the child, requirements for the educator, problems of the pedagogical intercourse and their solutions. The above analysis draws the main conclusion according to which all these school systems are interdependent; moreover, without the classical pedagogy and new pedagogical trends no contemporary modern school could come into existence. Furthermore, most methodological innovations of the modern foreign school are both the result of the pedagogical searchings and achievements of the beginning of the XX century, as well as the reflection of the past ideas on the present.